New species and records of Caenidae Newman, 1853 (Insecta: Ephemeroptera) from Northeastern Brazil - Nascimento, Stênio R. S.; Rodrigues, Jackson A. O.; Ale-Rocha, Rosaly; Lima, Lucas R. C. (Zootaxa, 2022)
New distributional records for four species and the description of a new species of Caenis Stephens from Parnaíba River Basin, in a semiarid region of the state of Piauí, Northeastern Brazil are given. Characters and illustrations to distinguish Caenis marataoan sp. nov. from all other species in Caenis are provided. The new species can be distinguished by the following combination of characters: 1) body length of male 1.5–2.0 mm, female 2.5–2.8 mm; 2) base of antennal flagellum not dilated; 3) forceps apically rounded, covered with trichomes and with 2–3 minute spines at apex; 4) styliger plate short with posterior margin convex; 5) penis fused and not laterally projected; 6) eggs oval-shaped; micropyle linear with narrow and long micropylar canal, preceded by an oval sperm guide.